Pengembangan model pembelajaran SKI berbasis nilai kepemimpinan sultan Muhammad Al-Fatih dalam pembentukan karakter disiplin dan tanggung jawab siswa madrasah ibtidaiyah - Komariyah, Aliyah Nur (Maliki Interdisciplinary Journal, 2026)
The quality of Islamic Cultural History (SKI) learning in Madrasah Ibtidaiyah continues to face challenges, particularly in developing students’ discipline and responsibility. This study analyzes the urgency of developing an SKI learning model based on the leadership values of Sultan Muhammad Al-Fatih through a literature study approach. The sources examined include classical works such as Imam Al-Ghazali’s thoughts on ethics and learning manners, as well as contemporary research related to character formation, Islamic historical figures, and value-based pedagogy. The findings show that the current dominant SKI learning model remains informative and memorization-oriented, making it less effective in internalizing character values. Al-Fatih’s leadership values discipline, trustworthiness, hard work, strategic intelligence, and moral steadfastness are highly relevant for elementary-level students. Integrating these values into instructional syntax consisting of value orientation, narrative exploration, reflective internalization, and character action can enhance the effectiveness of character education. It is concluded that an SKI learning model grounded in Al-Fatih’s leadership values is essential for strengthening character development in madrasah. Successful implementation requires teacher competence, meaningful learning media, and a supportive school culture.